(untitled) (Práxis Educativa, 2022)
This article results of a postdoctoral investigation that aimed to understand how the visual arts and the aesthetics arising from them contribute to colonization and/or decolonization processes. It is about a theoretical essay that explores some concepts and categories present in decolonial and freirian studies as a support for thinking about the visual arts and the aesthetics arising from them, based on a dialogue with the artist Francisco Brennand and his work. It is affirmed the need to understand art and the creative processes of images and different languages as dialogical paths and re-existence, as a possibility of confronting and overcoming colonial dictates. Keywords: Art. Decoloniality. Francisco Brennand. Paulo Freire.